Caracterización morfológica de hongos fitopatógenos en el cultivo de alcachofa (cynara scolymus), sector Anchilivi - Cotopaxi. 2014 - Miño Gallardo, Oswaldo Antonio (2015)
The present research with the theme "MORPHOLOGICAL CHARACTERIZATION OF MUSHROOMS FITOPATÓGENOS IN THE CULTIVATION OF ARTICHOKE (Cynara scolymus), SECTOR ANCHILIVI - COTOPAXI. 2014", was carried out in a fitopatología laboratory, the objective was to characterize the mushroom that causes the greatest impact in the artichoke production morphologically (Cynara scolymus), in the sector Anchilivi, canton Salcedo, County of Cotopaxi. The Work carried out by means insolation techniques in laboratory and then observe to the mushroom (it would Alternate cinerariae), in the electronic microscope to analyze their structures and then to ratify it with the existent bibliography. The fundamental aspects of this research are; The determination of the Mushroom fitopatógenos greater impact in the production of Artichoke (Cynara scolymus), which was determined by the revision and bibliographical discussion, achieving identify signs and symptoms of the mushroom in field, the technique used was the direct observation in the cultivation comparing and ratifying with the mentioned source, allowing us with this to carry out the macro and micro structures as: Talo, Micelio, Hifa, Septo, Conidióforo, Ascospora, ending up obtaining digital pictures with the use of a microscope Trinocular and a scientific camera, the same as using existing taxonomic key achieved confirm the presence of the agent which is (it would Alternate cinerariae), and it could describe its life cycle under controlled conditions carrying out the sowing and isolation of the pathogen with the use of boxes Petri in a means of cultivation potato - dextrosa - agar, and it remained in the incubation camera for the time of five days to a temperature of 22°C.